2013
DOI: 10.1080/10464883.2013.817164
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Informal Urbanism: Simulating Informal Settlement Practices in the Design Studio

Abstract: Informal settlements have become dominant forms and processes of urban development in many cities, yet the task of helping students engage with design issues in such contexts is fraught with difficulties of access, safety and complexity. Drawing on detailed fieldwork, this paper explores ways in which informal settlement formation can be taught in design studio through the use of games that simulate incremental practices of room-by-room accretion and prospects for transformation. The pedagogical goals are to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…This is by no means a prescriptive solution, but rather an illustration of a specific way to Different forms of urban informality have largely remained not only invisible on official maps and from the gaze of the formal city [48] but also underexplored in urban design education. There is only an emerging body of knowledge on incorporating informality in the built environment education [45,46,[49][50][51][52]. It has been pointed out that developing courses on urban informality can most effectively expose students and instructors to the ways in which different forms of informality work in cities and make them visible [46] (p. 449).…”
Section: Informality and Urban Design Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is by no means a prescriptive solution, but rather an illustration of a specific way to Different forms of urban informality have largely remained not only invisible on official maps and from the gaze of the formal city [48] but also underexplored in urban design education. There is only an emerging body of knowledge on incorporating informality in the built environment education [45,46,[49][50][51][52]. It has been pointed out that developing courses on urban informality can most effectively expose students and instructors to the ways in which different forms of informality work in cities and make them visible [46] (p. 449).…”
Section: Informality and Urban Design Educationmentioning
confidence: 99%
“…The second Urban Design Studio can explore how urban design can engage with practices of upgrading by drawing on evidence from an international Field Study Visit. While the issues of access and safety become critical in coordinating such Design Studios, practices of incremental housing, informal accretion and possible transformations can be simulated using games as well [51]. Both Design Studios can explore the understudied aspects of informality, including regulatory responses and spatial solutions to most effectively accommodate informality [41].…”
Section: Urban Design Studios On Informalitymentioning
confidence: 99%
“…More importantly, there is little research on the value and benefits of undertaking international planning studios or teaching approaches using similar terminology, such as studio abroad, global studios, travelling studios, and the like, in the Australian planning education landscape. In 2013, Owen, Dovey, and Raharjo observed that the major impediments to teaching students planning and design in offshore international studios are the difficulties of safety, settlement access, and the necessary skills required to understand city complexity [9]. experiences to their home settings where they live, thus drawing important comparative lessons on how cities are planned and the challenges of sustainable development in different contexts.…”
Section: The Importance Of the Studio In Planning Pedagogymentioning
confidence: 99%
“…Students typically work in small collaborative groups with multiple learning and teaching approaches [3]. However, there is minimal attention in the literature concerning international planning studios that expose students to understanding wider regional and global city contexts, as well as address pressing social and civic planning and sustainable development issues [9].…”
Section: Introductionmentioning
confidence: 99%
“…Informal housing, which is often part of overcrowded, poorly serviced, and unhealthy neighbourhoods, has proven to be the only affordable housing choice left for a significant part of the population in Global South [1]. In the absence of regulated and planned provision of upfront necessary infrastructure-i.e., water supply, sanitation systems, footpaths, and drainage-these services have to be retrofitted after housing has been built, into unplanned and dense conditions [2].…”
Section: Introductionmentioning
confidence: 99%